Posted by **Amir** on Monday, January 23, 2012 at 10:01am.

prove that (cotx+tanx)(cotx-tanx) = 1/(sin^2 x) - 1/(cos^x)

## Answer this Question

## Related Questions

- Math - 1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 ...
- Pre-Calc - How do I solve this? My work has led me to a dead end. tan(45-x) + ...
- trig - Verify the trigonometric identity. Please show all steps. tanx-cotx/tanx+...
- trig - verify the identity (tanx+cotx) (1) __________ = ______________ (tanx-...
- trig - verify the identity: tan^2x(1+cot^2x)=1/1-sin^2x Verify the Id: tanx + ...
- math - solve each identity algebraically 1)(1-tanx)/(1-cotx)=-tanx 2)(1+cotx)/(1...
- trig - (tanx+cotx)over(tanx-cotx)=(1) over sin^2x-cos^2x)
- Trig - Verify that each of the following is an identity. tan^2x-sin^2x=tan^2xsin...
- trig - {tan^2x+cotx divided by tanx-cotx} is equal to {1 divided by sin^2x-cos^...
- Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...